The Assessment of the Quality of Life in Children with Chronic Liver Disease - Demiral, Meliha; Başarır Özkan, Tanju; Özgür, Taner; Özkan, Bige; Erdemir Eren, Gülin; Altay, Derya (Turkish Journal of Gastroenterology, 2021)
Background: Improvement in the quality of life (QoL) of patients with chronic diseases is as important as medical care. This study aimed to evaluate the QoL of children with chronic liver diseases and to determine related factors. Methods: For this study, 101 children with chronic liver disease, 100 healthy controls, and their parents were included. The Pediatric Quality of Life Scale (PedsQL) was used to evaluate health-related QoL; higher scores indicate better QoL. Patients were evaluated before and after initiation of treatment and being educated about their illness. Results: The mean patient age was 12.9 ± 3.9 years. Total PedsQL scores of the patients and the healthy control group were 38.6 ± 18.9 and 55.4 ± 14.3, respectively (P = .01). The scores of the parents of the patient and control groups were 35.4 ± 14.2 and 54.0 ± 16.9, respectively (P = .02). Patient and parent scores were positively correlated. Significantly higher scores were found in the 5-10 age group compared to the 10-15 and 15-18 age groups in the psychosocial score category. An increase in the QoL scores of patients who were started on medication other than steroid treatment was observed in the sixth month of treatment (35.8 ± 13.4 vs. 33.6 ± 8.9, P = .01, respectively). Conclusion: Both children with chronic liver diseases and their parents have a perceived lower QoL than healthy peers. The effect of chronic liver disease on psychosocial health is more pronounced in children older than 10 years. The quality of life is inversely proportional to the severity of the disease. It was observed that primary or symptomatic treatments have a positive impact on the perception of QoL, with the exception of steroid treatment.